2017
DOI: 10.1111/cge.12968
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic protoporphyria a clinical and molecular study from Lebanon: Ferrochelatase a potential tumor suppressor gene in colon cancer

Abstract: Erythropoietic protoporphyria (EPP) is a rare cutaneous and systemic disease caused by mutations in the ferrochelatase gene (FECH). The molecular underpinnings of EPP in Middle Eastern populations and relative to other ethnic groups secondary to increased consanguinity are unknown. To understand the molecular pathogenesis of Middle Eastern EPP, we surveyed clinicopathological and molecular features in 6 large consanguineous families from Lebanon and Syria presenting with cutaneous and systemic features consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Currently, there are no available treatments for genodermatoses, such as MDM, causing patients to abandon long‐term clinical follow‐up, which result in missing some features of the condition that present late in the disease. Our group among others has had a long standing interest in understanding the molecular pathogenesis of genodermatoses in addition to unraveling uncommon clinical features of these diseases . In this report, we sought to study a consanguineous Middle Eastern family with clinical features of MDM, a rare autosomal recessive genodermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no available treatments for genodermatoses, such as MDM, causing patients to abandon long‐term clinical follow‐up, which result in missing some features of the condition that present late in the disease. Our group among others has had a long standing interest in understanding the molecular pathogenesis of genodermatoses in addition to unraveling uncommon clinical features of these diseases . In this report, we sought to study a consanguineous Middle Eastern family with clinical features of MDM, a rare autosomal recessive genodermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the RAS/MEK pathway increased PpIX accumulation in cancer cells by regulating the FECH activity mechanism, which would facilitate precise recognition of tumor boundaries and small satellite tumors [ 25 ]. Relevant studies have shown that changes in FECH expression were detected in human colon cancers and that loss of FECH has a tumor-suppressive effect on colon carcinogenesis in vitro [ 26 ], which was a potential tumor-suppressor gene for colon cancer [ 27 ]. The FECH gene may be a switch gene involved in the invasiveness of pituitary nonfunctioning adenomas [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of ferrochelatase, a terminal enzyme of the heme biosynthetic pathway, was markedly reduced in sun‐exposed fibroblasts relative to matched sun‐protected fibroblasts. Furthermore, SE fibroblasts were able to restore a normal phenotype when co‐cultured with SP fibroblasts 18 . Here, we studied a second form of cutaneous porphyria in an individual with severe autosomal recessive variegate porphyria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SE fibroblasts were able to restore a normal phenotype when co-cultured with SP fibroblasts. 18 Here, we studied a second form of cutaneous porphyria in an individual with severe autosomal recessive variegate porphyria. The aim of this study was to isolate and characterize the human skin-derived mesenchymal-like stem cells from different areas of the skin in autosomal recessive variegate porphyria patient (SE and SP) in comparison with the skin-derived mesenchymal-like stem cells from healthy individual and to determine whether stem cells in sun-protected region could be used to regenerate areas in the skin that are damaged.…”
Section: Introductionmentioning
confidence: 99%